Argumentación jurídica para incrementar un inciso en el art.189 del Código Integral Penal, que establezca el monto de la cosa sustraída en el delito de robo. - Gualpa Albuja, Marco Patricio (2015)
with the entrance in validity of the new Penal Integral Code, it is considered that it is framed inside the national juridical classification, and that the reformations carried out in the same one go with the limits of a constitutional State of rights and justice. Therefore it is necessary to consider the present grade thesis, since regarding the robbery crime, when not considering the value of the subtracted, to the moment to dictate a condemnatory sentence, the constitutional principle of proportionality is forcing. The present work proposes the increment of a parenthesis in which the pain is determined according to the value of the subtracted. In the empiric part of the present grade thesis it is based on the scientific observation and the documental analysis: and the historical-logical, analytic-synthetic, inductive-deductive methods. What is sought to get with the present work, is to give to know the artificial argument, to determine that people that are judged by the robbery crimes, should be considered the value of the subtracted, so that the sentence ¡s proportional with the | mount for the one that is accused in these crimes; in such a way that in all process the execution of the constitutional guarantees ¡s respected and of the due process, especially the established principle of proportionality in the numeral Art.76 of the Constitution of the Republic.